Deconstructing the Myth of the Megalophallus: The Cultural, Psychological, and Societal Implications of Hypermasculinity - Muzammal, Muhammad; Khan, Jabbar; Khan, Muzammil Ahmad (The Nucleus, 2025)
The idea of the megalophallus, or exaggerated male sexual organ, has travelled from ancient cultural symbols to its contemporary representations in media and pornography, directly influencing subjective perceptions of masculinity and male sexuality. This review seeks to deconstruct the megalophallus myth by discussing the cultural context surrounding the megalophallus from its genesis to current representation, and the associated mental health and gender identity implications associated with its mythologization. The megalophallus is a social myth that melds anatomy with power, sexual achievement, and masculinity and explicates the universality of these beliefs through historical, cultural, and media representations. The physiological context section provides a medical understanding of the reality of human differences in anatomy to tastefully debunk that larger genitalia results in better sexual satisfaction or sexual ability. The modern media and pornography section addresses how parts of male bodies and exaggerated representations of the male body in media and pornography relate to the myth, and eventually promulgate unrealistic ideals that lead to body image concerns and performance anxiety, and harmful understandings of masculinity. This review attempts to address the cultural, psychological, and social components of the megalophallus myth while cultivating a greater understanding of masculinity and sexuality that promotes a culture of different male expressions of identity, rather than being measured against inflexible and unrealistic ideals.